2023
DOI: 10.1038/s41598-023-33038-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the ORR after neoadjuvant therapy of TP regimen combined with PD-1 inhibitors for esophageal cancer

Abstract: The aim of this study is to evaluate the factors affecting the objective response rate (ORR) after neoadjuvant therapy of taxol plus platinum (TP) regimen combined with programmed cell death protein-1 (PD-1) inhibitors for esophageal cancer, and establish a predictive model for forecasting ORR. According to the inclusion and exclusion criteria, consecutive esophageal cancer patients who were treated in the First Affiliated Hospital of Xi’an Jiaotong University from January 2020 to February 2022 were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
0
1
Order By: Relevance
“… 28 Rulan Ma et al did not find that PLR metrics had predictive value for ORR in patients with locally advanced esophageal cancer treated with PD-1 inhibitors. 29 In our study, we found that PLR was probably an influencing factor for ORR and found no link between the two by further multifactorial analysis. Therefore, we believe that PLR is an important predictor of OS in ESCC patients.…”
Section: Discussioncontrasting
confidence: 53%
“… 28 Rulan Ma et al did not find that PLR metrics had predictive value for ORR in patients with locally advanced esophageal cancer treated with PD-1 inhibitors. 29 In our study, we found that PLR was probably an influencing factor for ORR and found no link between the two by further multifactorial analysis. Therefore, we believe that PLR is an important predictor of OS in ESCC patients.…”
Section: Discussioncontrasting
confidence: 53%